Effectiveness of Deep Learning in Digital-Based Learning Media: A Library Research Study in Indonesian Elementary Schools - Indana Farihatul Luthfi; Mundir Mundir; Nino Indrianto (Journal of Educational Sciences, 2026)
This study examines the effectiveness of deep learning as a pedagogical approach within digital-based learning media in Indonesian elementary schools. Employing a qualitative library research method, data were collected from academic books, peer-reviewed national and international journal articles, education policy documents, and credible digital sources. Data analysis followed three sequential stages: data reduction, data presentation, and synthesis, supported by source triangulation and peer review to ensure validity. The findings reveal that deep learning, characterized by meaningful, mindful, and joyful learning, demonstrates significant potential to improve the quality and inclusivity of educational experiences when integrated with digital media platforms such as Learning Management Systems, adaptive assessment tools, AI-based tutoring platforms, and gamified learning applications. The study further identifies a dual impact on student learning outcomes and teacher professional competence, as educators who receive structured digital training demonstrate greater pedagogical confidence and flexibility. Nevertheless, successful implementation requires equitable technological infrastructure, sustained teacher professional development, and curriculum alignment. This study concludes that deep learning and digital media integration represents a transformative educational strategy that demands systemic institutional commitment to realize its full pedagogical potential.